Racial Categorization and Intergroup Relations in Children: The Role of Social Status and Numerical Group Size - Gedeon, Cassandra; Badea, Constantina; Esseily, Rana (Frontiers in Psychology, 2021)
The aim of this review was to examine the effect of social and numerical group size on racial categorization and intergroup relations in children. We first described the development of racial categorization and the factors that increase the saliency of the race criterion in different contexts. Then, we examine the role of social status in intergroups relations and show that low status children express lower ingroup favoritism compared to their peers from high status groups. Few studies investigated the role of ingroup size on intergroup biases. Here, we look at this numerical variable through the proportion of children of different racial groups in the school environment. The results show that homogeneous environments contribute to the decrease of bias and negative attitudes. We discuss how identifying specific and interactive effects of the social and numerical group size would allow us to implement early and efficient intervention programs.